Chitosan nanoparticles for combined drug delivery and magnetic hyperthermia: From preparation to in vitro studies. (10th February 2017) - Zamora-Mora, Vanessa; Fernández-Gutiérrez, Mar; González-Gómez, Álvaro; Sanz, Beatriz; Román, Julio San; Goya, Gerardo F.; Hernández, Rebeca; Mijangos, Carmen
Highlights: Chitosan nanoparticles (CSNPs) were prepared through crosslinking with tripolyphosphate salts. Magnetic nanoparticles and 5-fluorouracyl (5-FU) were encapsulated within CSNPs. 5-FU release measured after 30 days decreases with magnetic nanoparticles content. CSNPs were successfully internalized over fibroblasts and A-172 cancer cells. CSNPs induced cell apoptosis by combination of magnetic hyperthermia and chemotherapy. Abstract: Chitosan nanoparticles (CSNPs) ionically crosslinked with tripolyphosphate salts (TPP) were employed as nanocarriers in combined drug delivery and magnetic hyperthermia (MH) therapy. To that aim, three different ferrofluid concentrations and a constant 5-fluorouracil (5-FU) concentration were efficiently encapsulated to yield magnetic CSNPs with core-shell morphology. In vitro experiments using normal cells, fibroblasts (FHB) and cancer cells, human glioblastoma A-172, showed that CSNPs presented a dose-dependent cytotoxicity and that they were successfully uptaken into both cell lines. The application of a MH treatment in A-172 cells resulted in a cell viability of 67–75% whereas no significant reduction of cell viability was observed for FHB. However, the A-172 cells showed re-growth populations 4 h after the application of the MH treatment when CSNPs were loaded only with ferrofluid. Finally, a combined effect of MH and 5-FU release was observed with the application of a second MH treatment for CSNPs exhibiting a lower amount of released 5-FU. This result demonstrates the potential of CSNPs for the improvement of MH therapies.